The Relationship Of Exclusive Asi Status With The Stunting Events In Ages 24-36 Months In The Belawan Village - Hutabarat, Eva Nirwana (SEAN Institute, 2023)
In infancy, the problem of stunting can be a serious problem if it’s not treated properly. Impacts that can be caused by stunting problems are metabolic disorders, decreased immunity, decreased cognitive abilities, impaired physical growth, and uncompetitive quality of work. Exclusive breastfeeding is one of the factors that can influence the prevalence of stunting because the nutrients contained in breast milk are one of the important factors that determine the period of development of children. This study aims to determine the relationship of exclusive breastfeeding with the incidence of stunting in toddlers aged 24-36 months in Belawan village. This type of research is a descriptive correlational study that is quantitative with a cross sectional approach. Sampling using a purposive sampling technique with a total of 44 respondents. This research instrument uses a questionnaire and microtoise/tape measure. Bivariate analysis using the chi square test. The history of exclusive breastfeeding in this study reached 56.8% or 25 children, and the majority of children in this study tended not to experience stunting. Children who get exclusive breastfeeding tend to experience stunting of 23 children (52.3%). The results of the chi square test obtained a value of p = 0,000 (p value <0.05) and r value = 0.609. The conclusion is that there is a relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 24-36 months in the Belawan village